Acute respiratory failure caused by phenytoin overdose - Kang, Chang Kyung; Kim, Min-Kyung; Kim, Min Jae; Jun, Kang Il; Kim, Ki Woong; Park, Seong-Ho; Song, Kyoung-Ho (The Korean journal of internal medicine, 2013)
KCI Citation Count: 0